2010
DOI: 10.3844/ajebasp.2010.160.168
|View full text |Cite
|
Sign up to set email alerts
|

Strategy in Turbulent Environment: A Case Study of Indian Domestic Company

Abstract: Problem statement: This case deled with an Indian pesticide company in the turbulent environment, which had to adopt a strategic shift due to changing environmental factors such as increasing competition from multinationals, regulatory forces, changing technologies. The case presented environmental situation in the industry and also described the events which led to the turbulency. Approach: This is a teaching case written with the objective to familiarize the students with concept of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The OCPs DDT, HCH, and Malathion accounts for about 71% of that used (Bhattacharyya et al, 2009;Narula and Upadhyay, 2010). Domestic consumption of pesticides in agriculture is low (0.5 kg.ha −1 ), 3.75% of global consumption, compared to 12.0, 7.0, 6.6, and 3.0 kg.ha −1 in Japan, the United States, Korea, and Germany, respectively (Chauhan and Singhal, 2006).…”
mentioning
confidence: 99%
“…The OCPs DDT, HCH, and Malathion accounts for about 71% of that used (Bhattacharyya et al, 2009;Narula and Upadhyay, 2010). Domestic consumption of pesticides in agriculture is low (0.5 kg.ha −1 ), 3.75% of global consumption, compared to 12.0, 7.0, 6.6, and 3.0 kg.ha −1 in Japan, the United States, Korea, and Germany, respectively (Chauhan and Singhal, 2006).…”
mentioning
confidence: 99%
“…Based on the background situation in Slovenia, it was concluded that to achieve longterm success must be based or focus also on several factors such as: corporate culture, values, and reward systems, state legislation, taxation systems, bureaucratic buffering, opportunities funding (partnership with banks, bank guarantees, venture capital, etc.). The strength of industrial competition shapes organizational resources and competitive strategies (Narula & Upadhyay, 2010). Meanwhile, competitive forces affect industries and companies and illustrate how domestic companies must reorient strategies to overcome environmental turbulence created by regulations, market forces and competitive forces (Saaty & Qureshi, 2011).…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Based on the background situation in Slovenia, it was concluded that to achieve long-term success must be based or focus also on several factors such as: corporate culture, values, and reward systems, state legislation, taxation systems, bureaucratic buffering, opportunities funding (partnership with banks, bank guarantees, venture capital, etc.). The strength of industrial competition shapes organizational resources and competitive strategies (Narula & Upadhyay, 2010). Meanwhile, competitive forces affect industries and companies and illustrate how domestic companies must reorient strategies to overcome environmental turbulence created by regulations, market forces and competitive forces (Saaty & Qureshi, 2011).…”
Section: Hypothesis Testingmentioning
confidence: 99%